E-School Implementation Using Radius Server and Authentication Mechanism - Astriani, Maria Seraphina; Pradono, Satrio (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Nowadays a lot of school would like to be a digital school or e-school. They may face lot of problems due to the sudden transition from conventional school to digitalized school. Some major problems are both lacks of human resources or man power and the basic knowledge about technology itself. Based on survey, the most common problem faced by most school is insecure wireless network. Even though they already installed advanced hardware, network security is still be the basic problem. No security mechanism such as encryption and authentication is the most common problem that may cause their network very vulnerable with any possible threat. After doing the research, Radius Server (both for authentication server and monitoring system) can help solve the problem.